ANALYSIS OF IMPLEMENTATION SUPPLY CHAIN MANAGEMENT MATERIAL PROCUREMENT EFFECT ON CONSTRUCTION PROJECT PERFORMANCE - Mayda Pahinggis; I Ketut Sucita (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
The implementation of material procurement supply chain management is very much needed by the construction industry to improve project performance. Supply chains can contribute to reduced costs, improve efficiency and improve the delivery of a material's final results promptly on time. So that it is expected to achieve the project objectives in accordance with the cost, quality and time. that had been planned. This research aims to determine the influence of the implementation of supply chain management of material procurement to the performance of construction projects and the biggest challenges in implementing supply chain management of material procurement. The analysis methods used in this study are descriptive methods and regression methods with quantitative approaches. Data collection techniques using a questionnaire and using a Likert scale. The number of respondents as many as 28 people selected from project employees with purposive sampling method. The results showed that the application of material procurement supply chain management characteristics had a positive and significant effect on the performance of construction projects by 39%. As well as the biggest factors that become challenges in implementing supply chain management of material procurement, namely the uncertainty of demand with an average of 2,797 and the smallest factor that becomes a challenge in implementing supply chain management of material procurement, namely internal uncertainty factor with an average of 2,202. Thus, from the results of the research, it is expected that the project can play a more active role in implementing supply chain management of material procurement to improve the performance of construction projects.